Cervical Cancer Vaccination: A New Hope (Anwer Khan Modern Medical College Journal, 2011)
Cervical cancer remains a threat which is second only to breast cancer in overall disease burden for women throughout the world. Organized screening with Pap cytology has made substantial reductions in cervical cancer morbidity and mortality in recent years. Establishment of genital human papillomaviruses (HPVs) as the etiological agent and invention of HPV vaccines now provide a great opportunity which could be useful in saving millions of lives in future. Initial Phase I, II and early phase III trials have shown promising results of this vaccine. This review article therefore is aimed to explore different aspects of this vaccine as well as to develop awareness among health professionals of different disciplines. Key Words: Cervical Cancer; Vaccination; Review DOI: 10.3329/akmmcj.v2i1.7468 Anwer Khan Modern Medical College Journal 2011; 2(1): 26-31